Dari Terra Sancta ke Terra Incognita: Dua Contoh Negosiasi Identitas Umat Kristen Purba - Anwar Tjen (Indonesian Journal of Theology, 2014)
This article is an attempt to learn from the struggle for identity in early Christianity. Since its birth from the womb of Judaism, Christianity was challenged to redefine its identity, rooted as it was in Judaism vis-à-vis the influence of Hellenization. Such a journey into unknown territory (terra incognita) unavoidably led to the birth of new identity which, on the one hand, remained an integral part of its original matrix, but at once challenged its exclusive character. In this overview, two main examples of reinterpretation are presented to illustrate the case, first, by Paul who radically reinterprets Torah and the identity of God's people in Christ, and second, by the author of 1 Peter who reinterprets the identity of "Christianos" as "aliens" and "exiles" in their Graeco-Roman milieu. As can be learned from these examples, negotiation, and renegotiation are an inevitable necessity when Christianity penetrates new territories in its encounter with the "other", in order to root itself in new terra incognita.